(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Digital transformation requires the world of education, especially in the field of Office Management and Business Services, to constantly adapt to the latest technological developments, including the application of Deep Learning. This community service activity aims to improve the literacy and competence of MGMP teachers in Magelang City in integrating the concept of Deep Learning into the curriculum and learning practices. The method used is gradual mentoring through training, assistance, and direct practice of compiling open devices based on artificial intelligence technology. The results of the activity show an increase in teachers’ understanding of the concept of Deep Learning, the ability to design relevant teaching materials, and readiness to apply technology-based learning in the classroom. This program is expected to support the creation of graduates who are adaptive and have 21st century skills, while strengthening the role of teachers as agents of digital education transformation at the vocational high school level.